Biometric Feature Template Security Schemes: An Overview - Manzoor, Sheikh Imroza; Selwal, Arvind (International Journal of Computer Sciences and Engineering, 2025)
Biometric systems are contemporary tools for human recognition, where the identity of the user is established by using his/her biological, behavioral or chemical characteristics. Biometric based systems are used to overcome many challenges of the traditional based systems. The important information of the biological traits of a user is stored into a database. In the recent past, it has been observed that the security of such biometric systems may be breached in many ways. In this paper, a brief review of various feature template security schemes has been presented. The presented study shows that template security scheme for a particular biometric system may not be suitable for its counterparts. Furthermore, it is revealed that the design of an efficient and accurate template security schemes for a biometric-based application satisfying all the ideal characteristics is still a challenge for the research community